A comparative genre analysis of Malaysian and English Court of appeal judgements / Ahmad Zaki Chamil - Ahmad Zaki , Chamil (2020)
This genre-based research examines and compares the rhetorical structures of Malaysia and England and Wales Court of Appeal judgements. This comparative genre study is motivated by a statement by the former Malaysian Judge of the High Court, Dato’ Syed Ahmad Idid and Umar A. Oseni (2011) in a writing guide book that presents a standard model to write legal judgements that can be adapted to all legal jurisdictions across the world. Normativity statements about the dos and don’ts on how to write judgements are valid and essential to the legal practices but this normative approach does not necessarily describe the compositional discoursal features and language use of legal judgements. Furthermore, a prescriptive standard model that can be adapted to all legal jurisdiction across the world might not reflect the actual comparative similarities and differences of legal judgements between legal systems. Consequently, Dato’ Syed Ahmad Idid’s and Umar. A. Oseni’s book presents a descriptive research prospect that could accompany the normative worldview of legal judgements. Following these motivations, twenty court of appeal legal judgements from the Malaysian and English legal system in the year 2017 are selected through purposeful (non-probabilistic) sampling. Adapting and modifying Bhatia’s (1993) framework, a bottom-up analysis is conducted to identify and categorize the rhetorical structures and communicative purposes of legal judgements from the Malaysia and English legal systems. The findings indicate that the legal judgements from both legal systems are generally identical at the higher level of communicative purposes and Moves and different at the lower level of Steps. Additionally, a new Move, ‘Introducing the Case’ is discovered in the legal judgements of both legal systems. Furthermore, expanding on the issue of linguistic resources, reporting type verbs in each Move of the legal judgements are categorized to determine their functions. Nine functional categories have been identified. However, the findings and conclusions of this research are limited to the selected twenty Court of Appeal legal judgements of Malaysia and England and Wales.